Idiopathic intracranial hypertension: is papilloedema inevitable?. Issue 3 (1st September 2002) - Wraige, E; Chandler, C; Pohl, K R E
Abstract : Headaches and papilloedema are key features of idiopathic (benign) intracranial hypertension (IIH). We describe three children in whom IIH was diagnosed in the absence of papilloedema. Recognition of atypical cases of IIH is important because pressure lowering treatment may be effective.